2020
DOI: 10.1021/acs.est.0c01540
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Photochemistry of Iron-Chloride Containing Particles as a Source of Aqueous Chlorine Radicals and Its Effect on Sulfate Production

Abstract: Photolysis of iron chlorides is a well-known photolytic source of Cl• in environmental waters. However, the role of particulate chlorine radicals (Cl• and Cl2 •–) in their multiphase oxidative potential has been much less explored. Herein, we examine the effect of Cl•/Cl2 •– produced from photolysis of particulate iron chlorides on atmospheric multiphase oxidation. As a model system, experiments on multiphase oxidation of SO2 by Cl•/Cl2 •– were performed. Fast sulfate production from SO2 oxidation was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 71 publications
6
32
2
Order By: Relevance
“…The large uncertainty arises from the uncertainties in the reaction kinetics. In addition to nitrate photolysis, it was found that photolysis of iron-chloride containing aerosol particles produces Cl•/Cl 2 • – that also lead to rapid multiphase oxidation of SO 2, with a γ SO2 of ∼10 –5 …”
Section: Laboratory Studies Of Reaction Pathways Of Current Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…The large uncertainty arises from the uncertainties in the reaction kinetics. In addition to nitrate photolysis, it was found that photolysis of iron-chloride containing aerosol particles produces Cl•/Cl 2 • – that also lead to rapid multiphase oxidation of SO 2, with a γ SO2 of ∼10 –5 …”
Section: Laboratory Studies Of Reaction Pathways Of Current Interestmentioning
confidence: 99%
“…In addition to nitrate photolysis, it was found that photolysis of iron-chloride containing aerosol particles produces Cl•/Cl 2 • − that also lead to rapid multiphase oxidation of SO 2, with a γ SO2 of ∼10 −5 . 109 Photosensitization chemistry is an emerging field in aerosol chemistry 110 that is founded in concepts explored originally in the natural waters photochemistry community. Solar radiation excites a photosensitizing molecule to a triplet state that can react with another molecule through energy transfer, electron transfer, or hydrogen atom abstraction mechanisms.…”
Section: Laboratory Studies Of Reaction Pathways Of Current Interestmentioning
confidence: 99%
“…167,168 These diacids, along with inorganic salts, influence the pH, ionic strength, water activity, and viscosity of the aerosol liquid water, and also compete for binding to iron, specifically the anionic species. 169 Using aerosol liquid water content of 6×10 -8 L m -3 of air, Gen et al 147 estimated the molar concentration of C2-C4 diacids to range from 3-95 mM depending on the diacid over a number of locations in 159,161,179 .…”
Section: Dicarboxylic Acidsmentioning
confidence: 99%
“…Hence, hydrophobic substrates are often used to study supersaturated aqueous droplets by reducing the particle and substrate contact area. Investigations on photochemistry can be easily performed by coupling a transparent substrate and an additional light source beneath the quartz window at a flow cell's bottom (Gen et al, 2019c(Gen et al, , 2020. A single particle can be retained for an infinite time deposited, facilitating studies of slow processes in the atmosphere.…”
Section: Deposited Particlesmentioning
confidence: 99%
“…4). Later, they also reported sulfate formation by multiphase oxidation of SO 2 during FeCl 3 photolysis (Gen et al, 2020). Recently, sulfate formation was used to indicate the synergistic effect of the coexistence of iron-organic complexes and nitrate under irradiation as a source of N(III), based on the reaction between SO 2 and N(III) (Gen et al, 2021).…”
Section: Multiphase Formation Of Secondary Inorganic Aerosols (Sias)mentioning
confidence: 99%